LINGUISTIC ERRORS ENCOUNTERED BY OVERSEAS STUDENTS FROM NON-ENGLISH SPEAKING COUNTRIES WHILE SPEAKING IN INDONESIAN - Putri, Aulia Nourma; Sri Gustiani; Yogi Widiawati (Journal of Innovation Research and Knowledge, 2024)
The number of overseas students from non-English speaking countries who are interested to continue their studies in Indonesia is increasing from year to year. They are enrolled in international classes together with Indonesian students in which all major courses are delivered in English. Outside the classrooms, however, those overseas students often use Indonesian language to communicate with their classmates and other Indonesian people. From the researchers’ observations, many overseas students made errors in using Indonesian language resulting in misunderstandings among the interlocutors. To address this issue, the researchers conducted a study to see what linguistic errors those overseas students encountered and the reasons associated with the errors. This qualitative descriptive study involved thirty overseas students from six different non-English speaking countries who are currently enrolled at State Polytechnic of Malang - Indonesia. Their conversations with their classmates and the broader community were used as the source of data. An interactive analysis model was used to analyze the data including data collection, data reduction, data presentation, and data verification. Several linguistic errors were found in this study, including errors in pronouncing words (phonology), forming words (morphology), constructing sentences (syntax), and choosing words that resulted in incorrect meanings (semantics). Besides, the contributing factors causing them to make the errors were: low motivation to learn the Indonesian language, the lack of support from their classmates and teachers, and limited time to learn Indonesian language.